Studi Komparasi: Implementasi Corporate Social Responsibility pada Berbagai Sektor Industri yang Tercatat di Bursa Efek Indonesia (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The implementation of corporate social responsibility (CSR) is not uniform in every industrial sector. The characteristics, challenges and expectations of stakeholders from each sector lead to different CSR approaches. This study aims to identify differences in CSR disclosure patterns between these sectors, and to assess whether these sectors tend to be more open in reporting their social responsibilities. This study uses a descriptive quantitative design by collecting secondary data in the form of annual reports of companies listed on the Indonesia Stock Exchange in 2020-2022. The sample consisted of 56 companies from various industrial sectors. The results showed that the energy and coal, consumer, property and construction sectors tended to focus more on CSR programs in environmental aspects and social. On the other hand, companies in the financial, health, technology, media and telecommunications sectors focused more on CSR programs in social and community aspects. The implications of this study are to add to the empirical literature on CSR practices in Indonesia, especially related to sectoral variations. This broadens the understanding of how certain industrial sectors tend to be more or less transparent in disclosing CSR activities. In addition, this study provides insight into corporate social responsibility and analysis for investors to invest in companies that carry out sustainability activities.